The moderating effect of self-motivation on the relationship between parent’s socio-economic background and children’s academic performance at Nigerian Universities - Isidore Ekpe; Mary Olufunmilayo Adelaiye; Ernest Ikechukwu Adubasim; Victor Chidiebere Adim (2014)
The purpose of this study is to examine the moderating effect of self-motivation on the relationship between parent’s socio-economic backgrounds on their children’s academic performance at Nigerian Universities, which has received little attention. Issues concerning University undergraduate youths have become a cause for concern among stakeholders in the project called ‘education in Nigeria’. Such issues like expulsion from school due to examination malpractice or cultism, withdrawal due to poor academic performance and production of half-baked graduates have forced many concerned people to question the role of teachers as well as parent’s socio-economic background. The paper adopted a survey methodology to solicit responses from 150 final year University students (2012/2013) of Business Faculties in the north, east and west regions of Nigeria; using stratified proportionate random sampling. After data cleaning, 130 data were analyzed using descriptive statistics and hierarchical regression. One of the results indicated that student’s self-motivation (hard work) and rich parental socio-economic background are needed to achieve academic success; though self-motivation appears to be a more critical success factor. The paper recommended that the government and the authorities of Nigerian universities should intensify effort at counselling the students on the need to study hard in order to achieve academic success rather than relying on their parents’ socio-economic background. This will improve teaching and learning in Nigerian Universities. The study is limited to University Business Faculties in Nigeria. Future studies can investigate other tertiary institutions in Nigeria.